Opinions of Students on Counseling Teachers' Efforts in Improving Learning Outcomes Low achieving students - Rimondro; Muhammad Dani Fauzan Sajid (International Journal of Pedagogy, 2023)
The purpose of this study was to describe students' opinions of the counseling teacher's efforts to improve the learning outcomes of low achieving students . The research method used is descriptive quantitative, with the technique of collecting funds using a questionnaire or questionnaire. The study population was all students of grades X and XI SMA Adabiah Padang totaling 575. The sample was drawn using a purposive sampling technique and was represented by 51 students. The results showed that the social self-concept of the youth at the Tunas Bangsa orphanage in Solok City in the orphanage environment was in the high category on average . This means that the views or assessments of the orphanage adolescents on their ability to interact with the leadership of the orphanage, the caretaker of the orphanage, and friends who live in the orphanage are positive. The social self-concept of the youth at the Tunas Bangsa orphanage in Solok City in the average school environment is in the high category . This means that the views or assessments of orphanage adolescents on their ability to interact with teachers, school personnel and friends at school are positive.